The need for an opening in the Historiography of the University of Alcalá - Gómez García, Gonzalo (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
The historiographic world of European universities over the last thirty years has been subjected to different perspectives of analysis that have gone beyond flat views in the search for understanding these educational institutions. In this context, the historiography of the University of Alcalá of the last three decades has revolved around the building universe of the schools as the only method of approach. This model has analysed only the Colegio Mayor de San Ildefonso and the minor ones -cisnerian, secular and regular-. Through this work we want to highlight the gaps that this method has left, as well as make specific proposals through the analysis of the faculties, to open the historiography of an institution that was key in the history of Castile and Spain for three centuries.